Value creation for competitiveness / Muhamad Saufi Ahmad - Ahmad, Muhamad Saufi (2001)
What's On The Plate : 1. Value And Value Creation 2. Value Creation And Competitiveness 3. Knowledge: The Nerve For Value Creation 4. Productivity Measurement Factor Of Value 5. HR: The Value Creator 6. ICT: The Enabler For Value Creation 7. Towards Value Creation: Case Experience 8. Digital Library Way To Knowledge And Value